2006
DOI: 10.1590/s1807-59322006000500016
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Archaeal Organisms in Development of Atherosclerotic Vulnerable Plaques and Myxoid Matrices

Abstract: HG, Canzian M. A role for archaeal organisms in development of atherosclerotic vulnerable plaques and myxoid matrices. CLINICS. 2006;61(5):473-8.PURPOSE: Vulnerable plaques are characterized by a myxoid matrix, necrotic lipidic core, reactive oxygen species, and high levels of microorganisms. Aerobic microbes such as Chlamydophila pneumoniae and Mycoplasma pneumoniae usually do not survive in oxidative stress media. Archaea are anaerobic microbes with powerful anti-oxidative enzymes that allow detoxification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
(41 reference statements)
1
11
0
2
Order By: Relevance
“…Co-infection with Mp and Cp was described in atheroma plaques for the first time by Higuchi et al [31]. This group also found higher numbers and a high correlation of Cp antigens and Mp DNA, and archaea-like microparticles in intimal association with Mp and Cp in vulnerable plaques, which might explain a local increased vessel inflammation and dilatation [32]. A similar atherosclerotic complication might be occurring in AAA lesions.…”
Section: Discussionmentioning
confidence: 74%
“…Co-infection with Mp and Cp was described in atheroma plaques for the first time by Higuchi et al [31]. This group also found higher numbers and a high correlation of Cp antigens and Mp DNA, and archaea-like microparticles in intimal association with Mp and Cp in vulnerable plaques, which might explain a local increased vessel inflammation and dilatation [32]. A similar atherosclerotic complication might be occurring in AAA lesions.…”
Section: Discussionmentioning
confidence: 74%
“…VP are known to be larger, with increased amount of lipid in the plaque, and thin fibrous cap [7]. This study showed, by electron microscopy, Microparticles (MPs) with electron lucent (EL) content, in close association with Mp bodies, mainly in myxoid matrix foci [8].…”
Section: Introductionmentioning
confidence: 81%
“…On the other hand, a symbiotic life between archaeal MPs with mycoplasma may lead to proliferation of mycoplasma and archaea, both are capable to oxidize entrapped lipoproteins increasing virulence of co-infected microbes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Na placa de ateroma, a associação entre Mycoplasma pneumoniae e Chlamydophila pneumoniae se associou à proliferação de ambos, com inflamação, degradação do colágeno e formação da placa vulnerável [10,11].…”
Section: A C B F E Dunclassified
“…Na valva aórtica, a proliferação de Chlamydophila pneumoniae e de Mycoplasma pneumoniae se associou à calcificação do tecido, com estenose da valva aórtica [11,50]. Roggério et al estudaram a relação entre Mycoplasma pneumoniae e Chlamydophila pneumoniae nos aneurismas de aorta e identificaram a presença destas bactérias na camada adventícia da aorta.…”
Section: A C B F E Dunclassified